Tanggung Jawab Hukum Perusahaan Terhadap Lingkungan Hidup Akibat Eksploitasi Galian C Ilegal Di Provinsi Sulawesi Utara - Febriana Veronika Nelwan; Sudiyana; Aisya (Fakultas Hukum Universitas Janabadra, 2026)
This study examines the legal responsibilities of companies towards the environment as a result of illegal C mining exploitation activities within the jurisdiction of the North Sulawesi Regional Police. The study focuses on civil law and business law aspects, positioning companies as legal subjects responsible for the environmental and social losses incurred. This study uses an empirical juridical method, with data obtained through interviews with relevant stakeholders. The legal analysis is based on Article 1365 of the Civil Code concerning unlawful acts, Articles 87 and 88 of Law Number 32 of 2009 concerning Environmental Protection and Management, and provisions regarding Corporate Social Responsibility (CSR) in the Job Creation Law. The results of the study indicate that many companies involved in illegal mining practices ignore legal obligations, both in terms of licensing and environmental restoration. Weak cross-sectoral oversight, the practice of negligence by local authorities, and the minimal use of civil law instruments are major obstacles in enforcing corporate responsibility. This study recommends strengthening civil lawsuits as a strategic instrument in enforcing environmental law, as well as the integration of the principles of social responsibility and business accountability in mining regulations. This effort is expected to encourage businesses to better comply with environmental regulations and actively contribute to sustainable development.